ANALISIS PERLINDUNGAN HUKUM TERHADAP KREDITUR SEPARATIS PEMEGANG HAK TANGGUNGAN YANG KEHILANGAN HAK EKSEKUSI DALAM PROSES KEPAILITAN: - Luqyana Khalda Salsabila; Sri Untari Indah Artati (Reformasi Hukum Trisakti, 2023)
The Central Jakarta Commercial Court issued a decision Number 15/Pdt-Lawsuit Lain-Lain/2019/PN.Niaga.Jkt.Pst regarding bankruptcy asset disputes that have a negative impact on PT Maybank Indonesia Tbk., as a separatist creditor holding Dependent Rights (HT). The problems in this writing is in the form of, "how is the legal consequences for PT Maybank Indonesia Tbk. in the bankruptcy process and how is the legal protection for PT Maybank Indonesia Tbk. in the bankruptcy process". The research uses a juridical-normative type that is descriptive. The data used are secondary data which analyzed by qualitative analysis, and conclusions are drawn deductively. The result are PT Maybank Indonesia Tbk. suffered losses due to the decision given. The loss obtained was in the form of the loss of authority of PT Maybank Indonesia Tbk. in the control and management of assets owned. This is consequence to the lack of consistency in the provisions of the Bankruptcy Law (UUK). In addition, this can happen because there is a norm conflict between the Law on Dependent Rights (UUHT) and UUK. PT Maybank Indonesia Tbk. also did not get proper legal protection due to differences in views with those of UUK regarding deadlines in the asset execution process.